Designing Augmented Reality-Based Learning Multimedia Using Demonstration Methods to Improve Student Cognition in Basic Computer and Network Subjects - Fadilah, Alvon; Setiawan, Wawan; Siregar, Herbert (Universitas Pendidikan Indonesia, 2022)
Basic Computer and Network subjects are compulsory subjects for the Computer and Network Engineering expertise program for class X. There are problems found during learning activity in this subject, such as less effective learning methods, the lack of variety in multimedia used by educators, a lack of understanding and student activeness in the learning process are. The aim of this study is to demonstrate a learning method assisted by multimedia learning based on Augmented Reality to determine the cognitive enhancement of students on the anatomy of computer hardware parts. This study used the Comprehensive Life Cycle model (SHM or Siklus Hidup Menyeluruh) model with students of the X grade Computer and Network Engineering Skills Program at SMK Harapan 1 Rancaekek as the sample. The results obtained from this study are: 1) Multimedia learning has obtained a percentage value of 87.32% which is interpreted